Unveiling the Therapeutic Potential of Banxia Xiexin Decoction in Alzheimer’s Disease: Insights From Network Pharmacology and Experimental Validation - Qin G; Song R; Sun J; Dai J; Wang W; Meng F; Wang D; Liu Z; Sun B; Li C (Drug Design, Development and Therapy)
Gaofeng Qin,1– 3,* Rongqiang Song,1,* Jingyi Sun,4 Juanjuan Dai,3 Wentao Wang,3 Fantao Meng,3 Dan Wang,3 Zhe Liu,1 Baoliang Sun,5 Chen Li3 1Department of Traditional Chinese Medicine, Binzhou Medical University Hospital, Binzhou, Shandong, People’s Republic of China; 2Postdoctoral Research Mobile Station, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People’s Republic of China; 3Medical Research Center, Binzhou Medical University Hospital, Binzhou, Shandong, People’s Republic of China; 4Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 5Second AfFIliated Hospital, Shandong First Medical University & Shandong Academy of Medical Sciences, Taian, Shandong, People’s Republic of China*These authors contributed equally to this workBaoliang SunShandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China, Email blsun@sdfmu.edu.cnChen LiMedical Research Center, Binzhou Medical University Hospital, Binzhou, Shandong, People’s Republic of China, Email lc_0625@163.comBackground: Alzheimer’s disease (AD) is associated with various pathological states for which there is no effective treatment. First documented in the Eastern Han Dynasty’s medical classic, “Treatise on Febrile and Miscellaneous Diseases” (200– 210 Anno Domini), Banxia Xiexin Decoction (BXD) stands as a quintessential approach to treating spleen ailments. Recent studies have shown BXD’s effectiveness in mitigating memory impairment associated with AD. Yet, the precise mechanisms underlying BXD’s action against AD require further exploration.Aim of the Study: To explore the important components of BXD in exerting anti-AD effects and the underlying molecular mechanisms using network pharmacology, metabolomics analysis, and in vitro and in vivo validation strategies. Initially, candidates for BXD’s application in AD therapy were identified through extensive database searches, followed by an analysis of protein-protein interactions (PPI). To elucidate BXD’s therapeutic pathways in AD, we engaged in Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) assessments. Further, we delved into BXD’s primary constituents through ultra-high-pressure liquid chromatography coupled with Q Exactive mass spectrometry and molecular docking techniques. Finally, AD-associated Aβ42-SY5Y cells and APPswe/PS1dE9 (APP/PS1) transgenic mice models were utilized to further determine the activity and mechanisms of BXD through various molecular or phenotypic assays and metabolomics analysis.Results: Our findings identified the PI3K/Akt signaling pathways as central to BXD’s effects. Using in vitro and in vivo models, we found the activity of BXD against AD to be mediated by the suppression of neuroinflammation and apoptosis, accompanied by activation of the PI3K/Akt pathway. Finally, we observed robust changes in metabolite levels in the plasma of BXD-treated APP/PS1 mice.Conclusion: Through systematic data analysis and experimental validation, the therapeutic advantages and fundamental molecular mechanisms of BXD in treating AD were revealed. These findings underscore the promising prospects and compelling potential of BXD, which targets the PI3K/Akt signaling pathway and inflammation, apoptosis, as a therapeutic strategy for improving AD. Keywords: banxia xiexin decoction, Alzheimer’s disease, network pharmacology, apoptosis, neuroinflammation, metabolomics